Novel phytosomal drug delivery systems in cancer therapy: advances, mechanisms, and translational potential - Sujatha Damera; Mounika Kuchukuntla; Mani Sharma; Ram Mohan Manda; Ananda Kumar Chettupalli; Rajendra Kumar Jadi (Creative Pharma Assent, 2026)
Background: Phytochemicals are medicinal plants with strong anticancer properties that alter various molecular pathways involved in tumor initiation, progression, and metastasis. Several adverse factors, however, hamper their clinical translation: low aqueous solubility, low membrane permeability, high first-pass metabolism, and rapid systemic elimination. Phytosomal drug delivery systems have emerged as a new, advanced lipid-based approach to addressing these pharmacokinetic and biopharmaceutical challenges. Methodology: Phytosomes are molecular complexes formed by a stoichiometric reaction between phytoconstituents and phospholipids, thereby increasing stability, improving bioavailability, and enhancing cellular uptake compared to conventional extracts and liposomal systems. Through meticulous analysis of articles from various publishers like PubMed, Science Direct, Elsevier, Bentham Science, Wiley, SAGE, Taylor and Francis publishers, and various indexing journals like Web of Sciences and Scopus databases, etc. Result and Discussion: This is a review of phytosomal technology in the treatment of cancers, including the principles of formulation, methods of preparation, physicochemical characterization, and the mechanisms of action of an increased anticancer effect. Conclusion: There is a critical discussion of preclinical and clinical evidence on phytosomal preparations of curcumin, silibinin, quercetin, catechins, and berberine. Further, present-day problems in translational research and regulation, as well as future opportunities, such as targeted and stimuli-responsive phytosomes, are also highlighted, indicating their potential as the next generation of phytomedicines in cancer therapy.